Investigating a new neocortical mask for Centiloid quantification. (20th December 2022) - Bourgeat, Pierrick; Dore, Vincent; Benzinger, Tammie L.S.; Tosun, Duygu; Li, Shenpeng; Goyal, Manu S.; LaMontagne, Pamela; Jin, Liang; Rowe, Christopher; Weiner, Michael W.; Morris, John C.; Masters, Colin L; et al.
Abstract: Background: The Centiloid (CL) project was developed to harmonise the quantification of Amyloid PET scans to a unified scale. The neocortical mask used for quantification was obtained using a private dataset of 19 mild AD patient and 25 older controls imaged using 11C‐PiB. The mean difference SUVR images were smoothed, subtracted and thresholded at 1.05 SUVR. While this threshold was chosen to maximise areas of specific Amyloid binding while avoiding areas of non‐specific binding, it was not evaluated in terms of agreement between different tracers or group separation. In this study, we created a new mask using an independent dataset of 11C‐PiB images, and investigated its impact on inter‐tracer agreement, tracer variability and group separation. Method: Using the AIBL and OASIS databases, 63 mild AD (MMSE=20‐24;CL>20) and 63 Healthy controls (MMSE>=28;CDR=0;CL<20) matched based on age and gender, were selected. Their 11C‐PiB images were spatially normalised using the SPM CL pipeline and transformed into SUVR using the whole cerebellum. A mean AD‐HC difference image was computed and thresholds of [0.6‐1.2] SUVR were explored. The resulting masks were evaluated in the 5 Amyloid tracers using the GAAIN head‐to‐head calibration datasets in terms of inter‐tracer agreement, variance in the young controls (YC) and YC‐AD effect‐size (ES). The recalibrated CL were evaluated on the AIBL dataset with the ES on the HC‐AD and HC‐MCI using baseline and rate of change (CL/yr). Result: Using a higher threshold resulted in a smaller neocortical mask, better targeting regions of high Amyloid update. In the GAAIN dataset, the smaller masks led to higher R 2 for each 11C‐PiB/18F‐Tracer pairs and higher YC‐AD ES. They also led to a lower variance in the YC for all tracers except for Flutemetamol. In AIBL, while it increased the ES at baseline, it decreased in the HC‐MCI when using CL/yr. Conclusion: While using a smaller neocortical mask improved inter‐tracer agreement and reduced variance in YC, the results in AIBL indicate that it might not be as sensitive to detect early changes as highlighted with poorer HC‐MCI ES.